(3GdWH GdbTWdis - (3GdbTWdjs
(3ChdgG (B:s
(3bGd GdeDda CeG HYO MeO Gddg MeOkG jSJMbg aCbhd Efg bO jLH Ydi ef (B( (3Yde (B) (3HYde ef GdYdhe GdfXQjI hLYd bUOg GdHGH GdChd fPcQ ajg ai Ci GdCeQGV jfHZi Cf jMei GdeQjV s
(3BNQgG (B:s
(3jfJgi HGdHGH GdYGTQ ai JOHjQ ScGa gPG GdaWQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B44s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQjO (B(5240/1) s
Keywords: (3GdWHs